EFFECTIVENESS OF ARECA CATECHU (BETEL NUT) EXTRACT ON THE MORTALITY OF AEDES AEGYPTI AND ANOPHELES LARVAE: A LABORATORY EXPERIMENTAL STUDY - Djamanmona, Rolyn Frisca; Kambu, Yowel; Kartikasari, Nurul; Mustamu, Alva Cherry (Universitas Nahdlatul Ulama Surabaya, 2025)
Background: Vector-borne diseases such as dengue fever and malaria continue to pose major global public health challenges. The increasing resistance of mosquito vectors to synthetic insecticides underscores the urgency for exploring plant-based larvicidal alternatives. However, the comparative efficacy of Areca catechu seed extract against Aedes aegypti and Anopheles spp. larvae remains insufficiently investigated. Methods: A laboratory-based experimental study employing a post-test only control group design was conducted. A total of 1,200 third-instar larvae (600 A. aegypti, 600 Anopheles spp.) were randomly assigned to six groups: five treatment groups (1000–10,000 ppm) and one negative control. Larvae were exposed to Areca catechu seed extract for 24 hours. Mortality data were analysed using one-way ANOVA with Bonferroni post-hoc tests, and LC₅₀ and LC₉₀ values were estimated via probit regression. Results: Larval mortality increased significantly with extract concentration (p < 0.001). At 10,000 ppm, mortality reached 100% in A. aegypti and 98% in Anopheles spp. Notably, A. aegypti exhibited greater susceptibility, with lower LC₅₀ values (3180.42 ppm vs 3536.55 ppm). These differences were statistically significant across nearly all concentration levels. Conclusions: Areca catechu extract demonstrates potent, dose-dependent larvicidal activity against two major mosquito vector species. This study addresses a critical gap by adopting a comparative cross-species approach, substantiating the larvicidal potential of bioactive phytochemicals such as arecoline, tannins, and saponins. Findings support the integration of plant-based larvicides into community-level vector control programmes, offering a sustainable and environmentally responsible alternative to conventional insecticides.